Dissemination of Religious Authority in 20th Century Indonesia - Jabali, Fuad (Studia Islamika, 2006)
The diversification of religious authority in Indonesia reflects not only the variety of Islamic orientation of religious communities in Indonesia but also shows the inability of the old religious authority to respond the increasing problems that the Indonesian Muslims communities have to deal with. Radical Muslims including Imam Samudra clearly does not show any respect to scholars/ulama such as the NU ulama, because, to him, they are unable to properly respond the suffering of the Muslims community in countries such as Iraq and Afghanistan. To him, the only authoritative ulama, whom Muslims should follow, are the ulama in the frontier (ulama mujahid).DOI: 10.15408/sdi.v13i1.580